Guns, germs, and stealing: exploring the link between infectious disease and crime - Shrira, Ilan (Evolutionary psychology, 2013)
Can variation in crime rates be traced to the threat of infectious disease? Pathogens pose an ongoing challenge to survival, leading humans to adapt defenses to manage this threat. In addition to the biological immune system, humans have psychological and behavioral responses designed to protect against disease. Under persistent disease threat, xenophobia increases and people constrict social interactions to known in-group members. Though these responses reduce disease transmission, they can generate favorable crime conditions in two ways. First, xenophobia reduces inhibitions against harming and exploiting out-group members. Second, segregation into in-group factions erodes people's concern for the welfare of their community and weakens the collective ability to prevent crime. The present study examined the effects of infection incidence on crime rates across the United States. Infection rates predicted violent and property crime more strongly than other crime covariates. Infections also predicted homicides against strangers but not family or acquaintances, supporting the hypothesis that in-group-out-group discrimination was responsible for the infections-crime link. Overall, the results add to evidence that disease threat shapes interpersonal behavior and structural characteristics of groups